Some aspects of religious views in the heritage of al-Farabi: research and scientific conceptions - Қaлиевa, Ш. С.; Хaвaн, A. (Journal of Oriental Studies, 2017)
In article studying of religious views of Abu Hasr al-Farabi by the Kazakhstan scientists is considered. In the chronological review published in Soviet period and years of independence of researches the main concepts which are put forward in their contents are defined.